Padre Bresciani nel “Cimitero di Praga”. Eco, riscrittura, citazione - Emiliano Picchiorri (Parole Rubate, 2011)
After exploring the abundance of quotations and allusions in Umberto Eco’s novel Il cimitero di Praga, this contribution focuses on the presence of passages from nineteenth-century serial narratives and in particular from L’ebreo di Verona by the Jesuit Father Antonio Bresciani. In Eco’s book, a long extract from this novel is delivered by Father Bergamaschi, a character whose biographical traits and psychological features could be related to Bresciani himself. However, the figure of the Jesuit author also lies behind another character, Father Pacchi, whose speech consists of quotations from L’ebreo di Verona. In these passages, Eco alternates between a type of rewriting aimed at linguistic modernization and the insertion of original details.